2013
DOI: 10.1007/s11434-012-5631-z
|View full text |Cite
|
Sign up to set email alerts
|

Tandem addition-cyclization reaction catalyzed by ytterbium chloride: An efficient one-step synthesis of 2-amino-4H-3,1-benzothiazine

Abstract: A clean, efficient method to synthesize 2-amino-4H-3,1-benzothiazines by ytterbium chloride-catalyzed tandem addition-cyclization reaction of o-aminocinnamate and isothiocyanates under solvent-free conditions is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Ethyl 2-(2-(phenylamino)-4H-benzo[d] [1,3]thiazin-4-yl)acetate (3a). 9 Following the typical procedure above, compound 3a (316 mg, 97%) was obtained as a white solid. The spectral data were in agreement with reported literature values: 1 H NMR (400 MHz, CDCl 3 ) d 7.57 (d, J ¼ 8.0 Hz, 2H), 3H),2H),7.09 (t,J ¼ 7.2 Hz,2H),6.71 (br s,1H),4.51 (dd,J ¼ 8.8,6.4 Hz,1H), 4.14 (q, J ¼ 7.2 Hz, 2H), 2.83 (dd, J ¼ 16.0, 8.8 Hz, 1H), 2.75 (dd, J ¼ 16.0, 6.4 Hz, 1H), 1.22 (t, J ¼ 7.2 Hz, 3H).…”
Section: General Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethyl 2-(2-(phenylamino)-4H-benzo[d] [1,3]thiazin-4-yl)acetate (3a). 9 Following the typical procedure above, compound 3a (316 mg, 97%) was obtained as a white solid. The spectral data were in agreement with reported literature values: 1 H NMR (400 MHz, CDCl 3 ) d 7.57 (d, J ¼ 8.0 Hz, 2H), 3H),2H),7.09 (t,J ¼ 7.2 Hz,2H),6.71 (br s,1H),4.51 (dd,J ¼ 8.8,6.4 Hz,1H), 4.14 (q, J ¼ 7.2 Hz, 2H), 2.83 (dd, J ¼ 16.0, 8.8 Hz, 1H), 2.75 (dd, J ¼ 16.0, 6.4 Hz, 1H), 1.22 (t, J ¼ 7.2 Hz, 3H).…”
Section: General Informationmentioning
confidence: 99%
“…In a recent publication, we described the synthesis of 2-amino-3,1-benzothiazines via the ytterbium chloride-catalyzed tandem addition-cyclization reactions of o-aminocinnamate with variety of different isothiocyanic esters. 9 The key intermediate in this particular reaction process was identied as a thiourea, which behaves as a nucleophile from its S-terminal to form the target product. Prompted by this result, we envisaged that the thiourea C could undergo an intramolecular cyclization reaction, in the presence of suitable metal catalyst, with either the S-terminal or the N-terminal of the thiourea behaving as the nucleophile to selectively form the 2-amino-3,1-benzothiazine A or 3,4dihydroquinazoline-2-thione B, respectively (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Benzoxazine derivatives exhibit interesting biological and pharmaceutical properties such as progesterone receptor modulator, anti-anxiety (etifoxine is an anxiolytic and anticonvulsant drug), anti-HIV, agonist, and antagonist activities (Figure A−B) . Whereas, benzothiazine skeletons are ubiquitous bioactive molecules and are well studied and extensively appealed in biochemical fields (Figure C–G). , Favorably, several related molecules such as 2-amino-4 H -1,3-benzothiazine scaffolds also allure unique biological properties and have secured increasing attention in medicinal chemistry. For example, it was investigated that 2-(4-piperidinamino)-4 H -1,3-benzothiazines (Figure D) displays appreciable cytoprotective properties toward the heart or neurons .…”
Section: Introductionmentioning
confidence: 99%
“…Several known desulfurization reagents include transition-metal salts such as CuCl 2 , NiO, HgO, , FeCl 3 , and Brønsted acids such as CF 3 CO 2 H and TfOH, and other reagents like TsCl/NaOH, LiOH/H 2 O 2 , polymer-supported carbodiimides, hypervalent iodine­(III), 1,10-(ethane-1,2-diyl)­dipyridinium bistribromide, and Ar 3 BiCl 2 . These reagents were extensively served for the synthesis of 1,3-benzoxazines and 1,3-benzothiazines. Moreover, these reported conditions suffer from disadvantages such as substrate scope, scalability, and the long reaction times. Therefore, the development of an efficient and easy to access approach for the preparation of 2-amino-1,3-benzoxazines and 2-amino-1,3-benzothiazines could be a useful tool in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of 4 H ‐3,1‐benzothiazines through thiobenzanilide intermediates was reported by Matysiak et al Xu et al reported the synthesis of 2‐amino‐4 H ‐3,1‐benzothiazine by a tandem addition‐cyclization reaction catalyzed by ytterbium chloride . The most general method for the synthesis of benzo[ d ]thiazine is the reaction between o ‐aminobenzyl chlorides and different thiocarboxamides benzopyran‐2‐thiones or thiourea .…”
Section: Introductionmentioning
confidence: 99%